Hearing voices : the gendered nature of mental health practices in New Zealand in the 1920s and 1940s : a thesis presented in partial fulfilment of the requirements of Master of Arts in Women's Studies at Massey University - Adams, Glennys Elaine (Massey University, 2007)
This thesis asks what insights can be gained from the oral histories of mental nurses and attendants about the gendered nature of mental health practices in New Zealand in the 1920s - 1940s. Previously recorded interviews provided the primary texts for analysis. In considering both their oral accounts and memories as constructions, feminist poststructuralist models are used to study the nurses' and attendants' experiences. Utilising gender as an analytical tool meant that the narrators' memories were understood as the gendered products of the interconnections between the practices and discourses of culture and individual subjectivity, and that gender was implicated in the practices and production of power in mental institutions. Discourse theory and practices provided the conceptual framework and methodology for an analysis that regarded knowledge as residing in and produced by discourses. By studying the different constructions of female nurses and male attendants in discourses of mental nursing it was possible to recognise how these representations legitimised and privileged particular kinds of knowledge and power. Contextualising the narratives socially and culturally enabled consideration of how the nurses and attendants reproduced dominant discourses of femininity and masculinity in circulation at the time they were working. The findings point to the way in which powerful discourses of gender predicated on the separation of women and men respectively into private and public spheres, intersected with gendered assumptions of mental illness and mental nursing. The oral testimonies show that the female nurses were situated between the paradigms of these discourses, but because subjectivities are not fixed and immutable, they adopted different and changing positions in relation to them at different times. Although it is argued that discourses of gender did shape the subjectivities of the nurses and attendants and were employed to support gendered institutional practices this was more complex than first appears. The voices of the female nurses can be heard sometimes embracing, sometimes resisting and sometimes transgressing gender norms.
Keywords: New Zealand; Psychiatric nursing; Psychiatric hospitals; Sex differences; History -- 20th century; Psychiatric nurses; Psychiatric aides